Vacant Lots Proposal - Tod Williams; Billie Tsien (Oz, 1989)
This proposal accepts the open lot as a positive addition/subtraction to the dense Manhattan city block. It recognizes the importance of openings to the interior of the typical block to bring additional light and air, to re-establish the relationship of interior court to exterior street and to expose the natural topographic features of the interior...